[OP.7B.10] EFFECT OF BARIATRIC SURGERY ON VASCULAR AND RENAL BIOMARKERS IN MORBIDLY OBESE, NORMOTENSIVE, NON-DIABETIC PATIENTS. (September 2016) - Bruno, R.; Vitolo, E.; Giannini, L.; Taddei, S.; Ghiadoni, L.; Solini, A.
Abstract : Objective: Aim of the study is to evaluate the effect of effect of bariatric surgery on vascular and renal biomarkers in morbidly obese, normotensive, non-diabetic patients. Design and method: 25 patients (19 women, age 44 ± 11 years, BMI 45 ± 7 kg/mq) were enrolled. A multidistrict vascular assessment was performed before and 12 months after bariatric surgery, including: aortic stiffness (carotid-femoral pulse wave velocity - PWV), endothelial function (flow-mediated dilation - FMD), carotid intima media thickness (cIMT) and distensibility coefficient (DC), and renal hemodynamics by means of renal resistive index (RI) in resting conditions and after sublingual administration of glyceryl trinitrite 25 mcg s.l. (DRIN) and renal plasma flow (123I-ortho-iodo-ippurate) Results: 20 patients completed the 12-month follow-up, showing a significant reduction in BMI (46 ± 7 to 31 ± 6 kg/mq, p < 0.001), blood pressure (BP - 127 ± 12 / 78 ± 11 to 117 ± 9 / 69 ± 7 mmHg, p < 0.05) and heart rate (71 ± 11 a 61 ± 10 bpm (p = 0.01). HDL was increased (da 41 ± 11 a 52 ± 9, p = 0.009) and triglycerides reduced (da 124 ± 56 to 76 ± 27 mg/dl, p = 0.005). Conversely, blood fasting glucose (100 ± 24 to 87 ± 9 mg/dl, p = 0.29), total cholesterol (da 180 ± 25 a 172 ± 40 mg/dl, p = 0.30) and serum creatinine (0.74 ± 0.17 to 0.69 ± 0.11, p = 0.52) were unmodified. FMD was increased (4.45 ± 2.20 to 6.91 ± 2.30%, p = 0.002), PWV (8.2 ± 1.1 to 7.4 ± 1.2 m/s, p = 0.04) and RI were reduced (0.62 ± 0.06 to 0.59 ± 0.06, p = 0.04), whereas IMT (0.69 ± 0.15 0.62 ± 0.14, p = 0.18), DRIN (−4.4 ± 4.3 to −6.0 ± 3.7%, p = 0.80) and DC (28.8 ± 9.3 to 37.8 ± 15.2, p = 0.11) where unchanged. Absolute changes in PWV, but not in FMD and RI, where directly correlated to changes in mean BP (r = 0.82, p < 0.001). Changes in PWV, FMD and RI were not associated to changes in BMI, HDL and triglycerides. Renal plasma flow before surgery was positively related to RI before surgery (r = 0.65, p = 0.03) and inversely related to changes in RI (p = −0.63, r = 0.04). Conclusions: Bariatric surgery causes an improvement in endothelial function and renal hemodynamics even in morbidly obese, normotensive, non-diabetic individuals with normal renal function, independent of the effect on BMI, BP and lipids. The increased RI observed before surgery may be a feature of hyperperfusion rather than of renal arteriolosclerosis, thus representing a functional and reversible alteration.